May Measurement Month 2019: an analysis of blood pressure screening results from South Africa. (20th May 2021) - Woodiwiss, Angela J; Gafane-Matemane, Lebo F; Norton, Gavin R; Uys, Lisa; Myburgh, Caitlynd; Nkeh-Chungag, Benedicta N; Kruger, Lizeth; Orchard, Ane; Peterson, Vernice R; Kolkenbeck-Ruh, Andrea; Ahiante, Blessing O; Phalane, Edith; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative of the International Society of Hypertension (ISH) aimed at raising awareness of high BP and acting as a temporary solution to the lack of screening programmes worldwide. As part of MMM, screening in South Africa in 2017 and 2018 revealed that approximately one-third of adults had hypertension, that only half of hypertensives were receiving anti-hypertensive therapy and that only a third of those with hypertension had controlled BP. These data highlight the need for continued screening and awareness campaigns. An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2019. Blood pressure measurements, the definition of hypertension and statistical analyses followed the MMM protocol. The sites screened were general populations, pharmacies, and university campuses in preference to hospitals and clinics, aiming to raise awareness, and allow access to screening to those less likely to be aware of their BP. Of the 4727 individuals (age 40.9 ± 18.1 years) screened, 31.9% had hypertension. Of those with hypertension, only 42.5% were aware and 36.1% were receiving treatment for hypertension. A large proportion (48.5%) of individuals receiving antihypertensive medication had uncontrolled BP. In conclusion, the high proportions of individuals unaware of their hypertension and with uncontrolled BP highlight the need for hypertension awareness campaigns and more rigorous management of hypertension.